2007
DOI: 10.1007/bf03177445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a compound drop on a dry surface

Abstract: The impact of a water-in-oil compound drop on a dry quartz surface was studied. The impact outcomes depended on a core-to-overall mass ratio and a Weber number. For a Weber number less than 570 and a core-to-overall mass ratio ranging from 0.07 to 0.7, five collision patterns were observed: complete deposition, shell deposition with core partial rebound, shell splash with core-shell deposition, shell splash with core partial rebound, and shell splash with core-shell partial rebound. Past research has indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Only a few studies have looked at the impact of compound drops on a solid surface (15)(16)(17)(18)(19)(20) or a liquid pool (21)(22)(23)(24)(25). Partial rebound of the impacting liquids after impact on a solid surface was observed by Chen et al (15) and Liu and Tran (18), but they did not explain the underlying mechanism. Complete rebound of the core and shell liquids was observed on a hot surface (26,27) due to the Leidenfrost effect (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have looked at the impact of compound drops on a solid surface (15)(16)(17)(18)(19)(20) or a liquid pool (21)(22)(23)(24)(25). Partial rebound of the impacting liquids after impact on a solid surface was observed by Chen et al (15) and Liu and Tran (18), but they did not explain the underlying mechanism. Complete rebound of the core and shell liquids was observed on a hot surface (26,27) due to the Leidenfrost effect (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, by jetting ouzo from the liquid column, we can produce such oil-lubricated drop in short time without waiting for the drop evaporation. This system might also be used for studying the impact dynamics of emulsion or compound droplets on the substrate as well as future applied studies.…”
Section: Resultsmentioning
confidence: 99%
“…One of the earliest studies on the impact of compound droplets observed their splashing and rebound behaviors upon impact on a flat, dry surface, which are also characteristic phenomena in single-phase droplet research. Nonetheless, the flow of the two phases within the compound droplet also gives rise to different impact dynamics, such as the ejection of the two phases during the spreading of water-in-oil compound droplets. , Additionally, a theoretical investigation of the maximal spreading feature of the impact was conducted using a three-phase numerical model .…”
Section: Introductionmentioning
confidence: 95%
“…Given their practical applications in the food industry, pharmaceutics, additive manufacturing, and energy utilization, compound droplets have garnered significant interest in recent years. 6,8,9 One of the earliest studies on the impact of compound droplets 10 observed their splashing and rebound behaviors upon impact on a flat, dry surface, which are also characteristic phenomena in single-phase droplet research. Nonetheless, the flow of the two phases within the compound droplet also gives rise to different impact dynamics, such as the ejection of the two phases during the spreading of water-in-oil compound droplets.…”
Section: ■ Introductionmentioning
confidence: 99%